Random Cards Berbantuan Wordwall pada Materi transfer Energi Antar makhluk Hidup untuk Meningkatkan Literasi Sains dan Self-Responsibility Siswa Kelas V UPT SDN Satriyan 03 Kabupaten Blitar - Lina, Karo; Fatih, Mohamad; Alfi, Cindya (MODELING: Jurnal Program Studi PGMI, 2024)
This research aims to develop Random Cards assisted by Wordwall as a learning media on the material of energy transfer between living things to improve science literacy and self-responsibility of fifth-grade students at UPT SDN Satriyan 03, Blitar Regency. The research method used is Research and Development (R&D). The research stages include preliminary studies, product development, product validation, and product testing. The results show that the Random Cards assisted by Wordwall media is effective in improving science literacy and self-responsibility of students. The science literacy score increased from an average of 65.5 in the pretest to 82.3 in the posttest. The self-responsibility score also increased from an average of 73.4 in the pretest to 87.1 in the posttest. It can be concluded that the Random Cards assisted by Wordwall media is suitable for use as a learning media to improve science literacy and self-responsibility of fifth-grade students.